Interventions of Teachers Applying the Principles of Inclusive Education in the Event of Outbreak of Impulsive Aggression in Students with Special Educational Needs (SEN) - Baranowska, Wanda (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Aggressive behaviour of students with SEN is a real challenge for teachers who follow the principles of inclusive education. A superficial judgement of such incidents by the society is easily disseminated, and weakens the teacher’s sense of competence and professional prestige. This article presents the results of a qualitative analysis of teachers’ statements regarding their effective and ineffective ad hoc interventions conducted against outbreaks of impulsive aggression of students with SEN.